Factores motivacionales que influyen en la selección de carrera de los estudiantes de la Facultad de Ciencias de la Educación, Humanas y Tecnologías UNACH - Medina Quinde, Fredy Hernán (2023)
Choosing a university degree in Ecuador is a complicated process for young people completing their last year of high school due to several motivational factors (extrinsic and intrinsic). This research aimed to determine the possible motivational causes that influenced first-time Faculty of Educational Sciences, Humanities, and Technologies UNACH students to select their major during the 2023-1S academic period. The research design was non-experimental, descriptive, bibliographic, and field type. For data collection, a 30-item questionnaire created from the instruments designed by Barreros (2019) and Cotrina (2019) was applied to a non-probabilistic sample of 203 students from the first semester of the Faculty of Education Sciences, Humanities, and Technologies from the National University of Chimborazo. It is determined that both extrinsic and intrinsic factors have a great influence when selecting a university degree. The intrinsic factor that most influenced students when choosing a university degree was personal interest in educating. On the other hand, the extrinsic factor that also greatly influenced first-time students was the improvement in the economic situation.